Moodle 3.x developer's guide : customize your Moodle apps by creating custom plugins, extensions, and modules - Wild, Ian (Birmingham, UK : Packt Publishing, 2017)
Effortlessly ensure your application's code quality from day 1 About This Book Customize your Moodle 3.x app. Leverage the new features of Moodle 3.x by diving deep into the Moodle development eco-system. Cater to heavy user traffic, customize learning requirements and create custom third party plugins. Who This Book Is For This book is for Moodle developers who are familiar with the basic Moodle functionality and have an understanding of the types of scenarios in which the Moodle platform can be usefully employed. You must have medium-level PHP programming knowledge. You should be familiar with HTML and XML protocols. You do not need to have prior knowledge of Moodle-specific terminology What You Will Learn Work with the different types of custom modules that can be written for Moodle 3.x Understand how to author custom modules so they conform to the agreed Moodle 3.x development guidelines Get familiar with the Moodle 3.x architecture - its internal and external APIs Customize Moodle 3.x so it can integrate seamlessly with third-party applications of any kind Build a new course format to specify the layout of a course Implement third-party graphics libraries in your plugins Build plugins that can be themed easily Provide custom APIs that will provide the means to automate Moodle 3 in real time In Detail The new and revamped Moodle is the top choice for developers to create cutting edge e-learning apps that cater to different user's segments and are visually appealing as well. This book explains how the Moodle 3.x platform provides a framework that allows developers to create a customized e-learning solution. It begins with an exploration of the different types of plugin.. We then continue with an investigation of creating new courses. You will create a custom plugin that pulls in resources from a third-party repository. Then you'll learn how users can be assigned to courses and granted the necessary permissions. Furthermore, you will develop a custom user home. At the end of the book, we'll discuss the Web Services API to fully automate Moodle 3.x in real time. Style and approach This book takes a step-by-step practical approach with every step explained in great detail using practical examples. You will create custom plugins from scratch with the examples shown and create new modules as well as extensions with the examples presented.
Moodle 3.x developer's guide : customize your Moodle apps by creating custom plugins, extensions, and modules -- About the Author -- Table of Contents -- Preface -- Chapter 1: Getting to Grips with the Moodle 3 Architecture -- Chapter 2: Moodle Plugins -- What Can I Plug In? -- Chapter 3: Internal Interfaces -- Chapter 4: Course Management -- Chapter 5: Creative Teaching -- Developing Custom Resources and Activities -- Chapter 6: Managing Users -- Letting in the Crowds -- Chapter 7: Creating a Dashboard -- Developing a Learner Homepage -- Chapter 8: Creating a New Skin -- Chapter 9: Moodle Analytics -- Appendix -- Index.
Description based on online resource; title from title page (Safari, viewed July 19, 2017).
Added to collection customer.56279.3
Keywords: Moodle; Moodle; Application software -- Development; Plug-ins (Computer programs); Logiciels d'application -- Développement.; Modules d'extension (Logiciels); COMPUTERS / Educational Software; Application software -- Development; Plug-ins (Computer programs)